A Review on Ecoli 0157: H7 (EHEC) (International Journal of Scientific Research and Management (IJSRM), 2023)
Escherichia coli O157:H7 is an important food borne and water borne pathogen is first isolated in 1982, shiga toxin. producing Ecoli O157:H7 which causes diarrhea, hemorrhagic colitis and haemolytic uremic Syndrome in humans. Haemolytic uremic. Syndrome (Hus) is a Serious condition and upto 50% of Hus patients can develop renal acute dysfunction or blood pressure. Ecoli 0157:H7 infects the alimentary tract and induces abdominal cramps with hemorrhagic diarrhea and it can be transmitted by person to person through fecal shedding and 11%. of infection are estimated. Enterotoxigenic Escherichia coli(ETEC) strain are the main cause of the diarrheal disease problems. ETEC strains are the bacteria which cause the acute watery diarrhea in chinldren. Diarrheagenic Ecoli infection are more common in Africa countries. The occurance of antimicrobial resistance depends upon the type of antimicrobialagent,bacterial strain,dose,time and mode of ministration. some of Ecoli 0517:H7 occurs after taking the undercooked meat or deficiency pasteurized dairy products. And some of Ecoli 0157:H7 occurs due ro exposal to contaminated water from potable drinking sources,pools and lakes and foods such as inappropriate washed leafy green vegetables and fruits,apple juice and direct contact with contaminated animals. Ecoli 0157:H7 shiga toxin causes leukocyte aggregation,platelet aggregation,microthrombin formation, apoptosis of affected cells ,renal dysfunction. shiga toxin not only effect kidney but it can also effect in diffuse vasculitic injuries which cause the effect on multiple organ system and organ failure.